Composite science and technology : selected, peer reviewed papers from the Eight International Conference on Composite Science and Technology (ICCST8), 22-24 March 2011, Kuala Lumpur, Malaysia - International Conference on Composite Science and Technology (8th : 2011 : Kuala Lumpur, Malaysia) 530985; Sapuan, S. M. 509363 (Stafa-Zurich, Switzerland ; Enfield, N.H. : Trans Tech Publications)
Includes bibliographical references and index